INTERFERON GAMMA EXPRESSION CD8+-T LYMPHOCYTE WITH ESAT-6-CFP-10 FUSION ANTIGEN STIMULATION BETWEEN ACTIVE TUBERCULOSIS, LATENT TUBERCULOSIS AND HEALTHY PEOPLE - Holland Lydia Marpaung; Betty Agustina; Jusak Nugraha; Fransiska Fransiska (Indonesian Association of Clinical Pathologist and Medical laboratory, 2018)
Tuberculosis (TB) is an infectious disease in the world causing a global problem. Vaccination with Purified Protein Derivative (PPD) still cannot prevent tuberculosis in Indonesia. Interferon-gamma (IFN-γ) produced by CD8+-T lymphocyte has an important role in eliminating Mycobacterium tuberculosis. The vaccine candidate antigenic test was done to observe the inducible ability of IFN-γ as a main protection cytokine. This study aim was to research the difference of IFN-γ expression CD8+-T lymphocyte percentage with ESAT-6-CFP-10 fusion antigen stimulations as a TB vaccine candidate. This research is a quasi-experimental study design in the laboratory by ESAT-6-CFP-10 fusion antigen-stimulated Peripheral Blood Mononuclear Cells (PBMC) culture in vitro in TB patients, latent TB, and healthy subjects’ groups. IFN-γ expression CD8+-T lymphocyte percentage were examined by flow cytometry BDFACSCalibur with results: without antigen fusion stimulation IFN-γ expression CD8+-T lymphocyte percentage mean (TB patients 2,560, latent TB 2,173, and healthy people 2,153) and with antigen fusion (TB patients 3,039, latent TB 2,471, and healthy people 2,405). There was no significant difference in fusion antigen stimulation PBMC between TB patients, latent TB, and healthy subjects’ group, and also within groups.